SOSIALISASI PENGENALAN INDUSTRI 4.0 PADA BIDANG TEKNOLOGI PERTANIAN UNTUK SISWA SEKOLAH MENENGAH PERTAMA DI KOTA PAGAR ALAM - Padya, Inka Rizki; Erika, Desta Ria; Syahputra, Asep (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Pagar Alam City is one of the cities located in South Sumatra Province and is a city producing vegetables and other agricultural commodities. Agricultural products in the city of Pagar Alam, have not been much touched by technological processes because of limited knowledge and lack of interest in learning new things. Therefore, to increase the knowledge of the people of the city of Pagar Alam, it can be done in the next generation, namely teenagers. Adolescence is a period of transition from children to adults. As the next generation of the nation, youth must know about technological advances. This community service aims to provide education to junior high school students as the nation's successors regarding industry 4.0, especially in the field of agricultural technology. The era of the industrial revolution 4.0 is an era of information and technology that influences the field of agricultural technology, with rapid changes.